^JKIES Nguyễn^
25 tháng 11 lúc 11:44
\(-TH1:\left|x-\dfrac{2}{3}\right|=x-\dfrac{2}{3}\\ =>\left(x-\dfrac{2}{3}\right)-\dfrac{5}{6}=0\\ =>x-\dfrac{2}{3}=\dfrac{5}{6}\\ =>x=\dfrac{5}{6}+\dfrac{2}{3}\\ =>x=\dfrac{5+2.2}{6}\\ =>x=\dfrac{3}{2}\\ -TH2:\left|x-\dfrac{2}{3}\right|=\dfrac{2}{3}-x\\ =>\left(\dfrac{2}{3}-x\right)-\dfrac{5}{6}=0\\ =>\dfrac{2}{3}-x=\dfrac{5}{6}\\ =>x=\dfrac{2}{3}-\dfrac{5}{6}\\ =>x=\dfrac{-1}{6}\)Vậy \(S=\left\{\dfrac{3}{2};-\dfrac{1}{6}\right\}\)
Đọc tiếp
Bình luận (0)
POP POP
25 tháng 11 lúc 11:47

loading...

Bình luận (0)

Các câu hỏi tương tự
Nguyễn Khôi  Nguyên
Xem chi tiết
vu duc huy
Xem chi tiết
Đinh Thị Mỹ Hạnh
Xem chi tiết
Chu Ngọc Huyền
Xem chi tiết
Han Rosie
Xem chi tiết
Trần Hiếu Anh
Xem chi tiết
hoàng phạm
Xem chi tiết
Hoàng Quốc Chính
Xem chi tiết
Phương Thúy Ngô
Xem chi tiết
Thảo Nguyễn Phương
Xem chi tiết

Khoá học trên OLM (olm.vn)


Khoá học trên OLM (olm.vn)